KOMUNIKASI PEMASARAN TERPADU TERHADAP BRAND AWARENESS - Yulianti Keke (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
This study is to identify and explain how the influence of Integrated Marketing Communications consists of Advertising, Sales Promotion, Personal Selling, Public Relations, and Direct Marketing, together and partially through Brand Awareness can influence the students to choose their universities. The method of the study is explanatory research which is using questionnaires as the research instruments distributed to169 respondents who are students of STMT Trisakti 6 Semester. Their area of high school is in East Jakarta before entering STMT. The results showed that variables of Integrated Marketing Communications like Advertising, Sales Promotion, Personal Selling, Public Relations and Direct Marketing, all together influence the brand awareness. Only Public Relations had asignificant effect on Brand Awareness.